Effects of tourism and globalization on land cover and the influence on the quality of life of Paphos area in Cyprus - Italos, Chrysostomos; Akylas, Evangelos; Hadjimitsis, Diofantos G. (My University, 2014)
Since 1960 most of the coastal area cites across the Mediterranean Sea concentrates people due mass immigration of people from the rural to urban areas. The extensive tourism development especially across the coastal areas, create demand of infrastructures and new work positions and intensive pressure to the environment. The new spirit of the globalization creates movability of people and goods around the word. The free transfer of people from countries with big population and low economical wealth, which are moved to areas where they can work. All the above generate demands of labor and Paphos is one of these areas where during the last decades was transformed from a small agriculture village in one excellent tourist destination. Across the coastal areas big tourist infrastructure was built and lot of different people travel from all areas around the word especially during the summer months. All these generate continuous changes to the environment, to the people and the society. The globalization of the universe commerce and the free transfer of goods and people modify the community stratification. The inflow of agricultures products from third countries reduces the local production and generates degradation and desertification of the rural areas. The periodical variation of the population of the area during the summer and winter periods affect to the environment. The increment demand of sources (water, energy and food) during the summer months pressurize the coastal strip area. By estimating a ratio of inflows by the outflows of goods, people and services of the study area and a ratio of the tourists by the local population, a general index can by arise which will clarify the effects on the environment on the study area. This paper presents the results obtained by this study by examining the effects of tourism on land cover and effects on quality of life for the Paphos area in Cyprus. The authors explores the potential of blending in the sustainability study the use of remote sensing especially on the land-cover effects.
Keywords: Environmental effects; Environmental planning; Globalization; Land cover; Quality of life; Sustainability index; Tourism sustainable development